THU0396 The Efficacy of Hydroxychloroquine for Obstetrical Outcome in Anti-Phospholipid Syndrome: Data from a European Multicenter Retrospective Study. (9th June 2015) - Mekinian, A.; Lazzaroni, M.G.; Kuzenko, A.; Alijotas-Reig, J.; Ruffatti, A.; Levy, P.; Canti, V.; Bremme, K.; Bezanahary, H.; Bertero, T.; Dhote, R.; Maurier, F.; et al.
Abstract : Background: Despite aspirin-LMWH combination, 10-15% of APS experience pregnancy losses and constitute the refractory obstetrical APS. Methods: We analyzed the outcome of pregnancies treated by hydroxychloroquine in patients with APS or asymptomatic antiphospholipid antibodies (aPL) carriers in European study. Results: Thirty patients with APS with 35 pregnancies treated by hydroxychloroquine were analyzed. Comparing the outcome of pregnancies treated by the addition of hydroxychloroquine to previous pregnancies under the conventional treatment, pregnancy losses decreased from 81% to 19% (p<0.05), without differences in the associated treatments. Among all 30 APS patients, thirteen patients with isolated obstetrical APS (primary APS in 12 cases) experienced 14 pregnancies under hydroxychloroquine. Among them, 5/14 experienced before hydroxychloroquine-treated pregnancy foetal losses or early preeclampsia without any treatment, and 9/14 experienced previous pregnancies losses with aspirin and/or LMWH. After the addition of hydroxychloroquine (400 mg/day [200-400]), the pregnancies losses decreased from 12/14 (86%) to 4/14 (29%) (p<0.05). Six APL carriers, with associated autoimmune disease in 3 cases (rheumatoid arthritis, undifferentiated connective tissue disease and Sjogren's syndrome) experienced 10 pregnancies under hydroxychloroquine (with median amount 200 mg/day [200-400]). Among the 10 pregnancies under hydroxychloroquine, associated treatments were used in all cases (aspirin alone in 6 cases, aspirin-LMWH and aspirin with prednisone in 2 cases each) and 8 (80%) resulted in live-born babies. Five patients with purely thrombotic APS (undifferentiated connective tissue disease in 2 cases) experienced 5 pregnancies under hydroxychloroquine. All five pregnancies were treated with aspirin-LMWH and hydroxychloroquine at 200 mg/day [200-400] and all resulted in live-born babies. Six patients with primary mixed APS (thrombotic and obstetrical APS) experienced 6 pregnancies under hydroxychloroquine (median amount 400 mg/day [200-400]). Five patients have previous pregnancies with aspirin-LMWH which all resulted in pregnancies losses. All pregnancies after the addition of hydroxychloroquine resulted in 6 live-born babies. Considering 14 patients with previous refractory obstetrical APS (n=5 with obstetrical and thrombotic primary APS and n=9 with purely obstetrical APS), all with previous pregnancies losses under treatment (aspirin with LMWH in 11 cases and LMWH in 3 cases), the addition of hydroxychloroquine resulted in live born babies in 11/14 (78%) cases (p<0.05). Conclusions: Our study shows the benefit of hydroxychloroquine addition in patients with refractory obstetrical APS and raises the need of prospective studies to confirm our preliminary study. Acknowledgements: We thank European Forum on Antiphospholipid Antibodies and SNFMI Disclosure of Interest: None declared